ANALYSIS OF THE USER PROFILE AS A TOOL FOR THE DECREASE OF ABANDONMENTS IN SPORTS CENTERS - Proaño Grijalva, María Alejandra; Martínez Cevallos, Daniel Alejandro; Alguacil Jiménez, Mario (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing CongressDO - 10.36779/mktdescubre/v#.#, 2020)
The high competition between sports companies, together with the knowledge and demands of users, drives sports managers to innovate and improve management systems in order to meet the existing demand and to accomplish the users´ expectations. This research attempts to analyze the user´s profile and preferences towards sports centers, as well as, the dropouts´ reasons, so as to verify whether there is any relationship between gender and the variables of age, frequency of attendance and dropouts´ reasons. The sample was made up of 111 users who completed a structured questionnaire of 6 blocks. A descriptive analysis was performed with SPSS version 25 followed by a chi-square test. The results revealed that women have a higher attendance frequency than men, a greater preference for the pool as an element to be attached to a sports center, and a higher dropout rate, mainly due to the lack of time. Furthermore, it was demonstrated that there is a significant relationship between gender and age of sports center users, while there is no significant relationship with frequency nor with dropouts´ reasons.